2004
DOI: 10.1159/000080126
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed Diseases in Patients with Dementia – A Potential Target Group for Intervention

Abstract: Objective: To study undiagnosed diseases in older people with and without dementia. Design: Cross-sectional population-based study in Lieto, southwestern Finland. Participants: All the inhabitants aged 64 and more in Lieto. Participation rate was 82% (n = 1,260). Measurements: Dementia and its subtypes were diagnosed according to prevailing criteria. Medical conditions were assessed in clinical examinations and from medical records. Results: 112 patients with dementia were found; 66% of them had at least 1 und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 74 publications
5
60
1
1
Order By: Relevance
“…Table 13). Data were collected from medical records in seven studies, 12,14,91,127,137,142,144 from clinical examination or interviews in six studies 1,101,118,119,128,134 and from a mixture of medical records and clinical examination in three studies. 2,121,143 The presence of dementia and comorbid medical conditions was assessed using a variety of measures (see Appendix 4, Table 14).…”
Section: Description Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 13). Data were collected from medical records in seven studies, 12,14,91,127,137,142,144 from clinical examination or interviews in six studies 1,101,118,119,128,134 and from a mixture of medical records and clinical examination in three studies. 2,121,143 The presence of dementia and comorbid medical conditions was assessed using a variety of measures (see Appendix 4, Table 14).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Thirteen studies reported the prevalence of diabetes in populations of people with dementia 2,12,14,91,118,119,121,127,128,142,143 or MCI. 101,134 Prevalence rates varied from 6% to 39%.…”
Section: Diabetesmentioning
confidence: 99%
See 3 more Smart Citations